A Comprehensive Analysis of Calmodulin-Like Proteins of Glycine max Indicates Their Role in Calcium Signaling and Plant Defense Against Insect Attack - Yadav, Manisha; Pandey, Jyotsna; Chakraborty, Amrita; Hassan, Md. Imtaiyaz; Kundu, Jiban Kumar; Roy, Amit; Singh, Indrakant Kumar; Singh, Archana (Frontiers in Plant Science, 2022)
The calcium (Ca2+) signalling is a crucial event during plant-herbivore interaction, which involves a transient change in cytosolic Ca2+ concentration, which is sensed by Ca2+-sensors, and the received message is transduced to downstream target proteins leading to appropriate defence response. Calmodulin-like proteins (C.M.L.s) are calcium-sensing plant-specific proteins. Although C.M.L.s have been identified in a few plants, they remained uncharacterized in leguminous crop plants. Therefore, a wide-range analysis of C.M.L.s of soybean was performed, which identified 41 true C.M.L.s with < 50 % similarity with Arabidopsis C.M.L.s. The phylogenetic study revealed their evolutionary relatedness with known C.M.L.s. Further, identification of conserved motifs, gene structure analysis and identification of cis-acting elements strongly supported their identity as members of this family and their involvement in stress responses. Only a few Glycine max calmodulin-like proteins (GmCMLs) exhibited differential expression in different tissue types, and the rest had minimal expression. Additionally, differential expression patterns of GmCMLs were observed during Spodoptera litura –feeding, wounding and phytohormone treatments, indicating their role in plant defence. The three-dimensional structure prediction, identification of interactive domain and docking with Ca2+ ions of S. litura-inducible GmCMLs indicated their identity as calcium sensors. This study on the characterization of GmCMLs provided insights into their roles in calcium signalling during plant-herbivore interaction.